#3**+4 **

f(something) = -3, so, from the graph, something1 = 0 and something2 = -4

”something” is f(f(x)), so f(f(x)) = 0 and -4

This means f(somethingelse1) = 0 and f(somethingelse2) = -4

Fom the graph we see somethingelse1a = 2 and somethingelse1b = -6

Also somethingelse2 = -2 (only one value)

This means f(x) = 2, -6, -2

When f(x) = 2, x = 3 and -7

f(x) never reaches -6

When f(x) = -2, x = 1 and -5

So sum = 3 - 7 + 1 - 5 = -8

Alan Jan 31, 2019

#3**+4 **

Best Answer

f(something) = -3, so, from the graph, something1 = 0 and something2 = -4

”something” is f(f(x)), so f(f(x)) = 0 and -4

This means f(somethingelse1) = 0 and f(somethingelse2) = -4

Fom the graph we see somethingelse1a = 2 and somethingelse1b = -6

Also somethingelse2 = -2 (only one value)

This means f(x) = 2, -6, -2

When f(x) = 2, x = 3 and -7

f(x) never reaches -6

When f(x) = -2, x = 1 and -5

So sum = 3 - 7 + 1 - 5 = -8

Alan Jan 31, 2019